2014
DOI: 10.3232/sjss.2012.v2.n3.04
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of soil heating on soil cations using the degree-hours method .

Abstract: Important factors in the evaluation of fire severity are the duration of the soil exposition to a certain temperature as well as the factors that determine the thermal transmissivity on the soil (moisture, texture, organic matter content, etc.). The aim of this work was to apply the degree-hours method (DH) to characterize the thermal impact of forest fires in soils. Thermal treatments in the laboratory were conducted using soil samples in order to study the effects in the soil exchange complex. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Following are the definitions for wildfire intensity and wildfire severity as used in this review, as well as other relevant wildfire and rainfall simulation terms. Wildfire Intensity: is typically a quantitative characterization of energy, such as the amount of fuel burned (e.g., units of g), the rate of fuel burned (e.g., units of g/s or W/m2) 22,51 , or peak temperature (e.g., units of °C) 24,48,49,[52][53][54] . This allows for explicit…”
Section: -Terminologymentioning
confidence: 99%
See 4 more Smart Citations
“…Following are the definitions for wildfire intensity and wildfire severity as used in this review, as well as other relevant wildfire and rainfall simulation terms. Wildfire Intensity: is typically a quantitative characterization of energy, such as the amount of fuel burned (e.g., units of g), the rate of fuel burned (e.g., units of g/s or W/m2) 22,51 , or peak temperature (e.g., units of °C) 24,48,49,[52][53][54] . This allows for explicit…”
Section: -Terminologymentioning
confidence: 99%
“…Propane torches typically produce peak soil surface temperatures of 500-600°C 54,61 whereas heat lamps produce peak temperatures of 200-400°C 90 from 5 to up to 220 minutes of exposure 54,61 , representing a range in burn intensities. The temperature gradient extending down through the soil surface in these experiments is typically measured using thermocouples placed 0-15 cm below the soil surface 22,24,29,54,61,103 . Studies reported a wide range of significant responses to burning: soil and water chemical constituents increased or decreased ~10-700% and hydraulic and water repellent properties changed by ~60-200% at ~1-3 increments of burn intensities each 62,89,121 .…”
Section: -Propane Torches and Heat Lampsmentioning
confidence: 99%
See 3 more Smart Citations